2014
DOI: 10.1016/j.jspi.2013.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Total interaction index: A variance-based sensitivity index for second-order interaction screening

Abstract: Sensitivity analysis aims at exploring which of a number of variables have an impact on a certain response. Not only are the individual variables of interest but also whether they interact or not. By analogy with the total sensitivity index, used to detect the most influential variables, a screening of interactions can be done efficiently with the so-called total interaction index (TII), defined as the superset importance of a pair of variables. Our aim is to investigate the TII, with a focus on statistical in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 18 publications
(36 reference statements)
0
16
0
Order By: Relevance
“…An unbiased and nonnegative estimate is especially valuable. When the true GSI is zero, an unbiased nonnegative estimate will always return exactly zero as Fruth, Roustant, and Kuhnt (2012) remark. The Sobol' index τ 2 u is of square form, but τ 2 u is not.…”
Section: Squares and Sums Of Squaresmentioning
confidence: 97%
See 1 more Smart Citation
“…An unbiased and nonnegative estimate is especially valuable. When the true GSI is zero, an unbiased nonnegative estimate will always return exactly zero as Fruth, Roustant, and Kuhnt (2012) remark. The Sobol' index τ 2 u is of square form, but τ 2 u is not.…”
Section: Squares and Sums Of Squaresmentioning
confidence: 97%
“…Theorem 2.2 leads to a sum of squares for u |u|σ 2 u . Liu and Owen (2006) express the superset importance measure as a square: Fruth, Roustant, and Kuhnt (2012) find that a sample version of (4.1) is the best among four estimators of Υ 2 u . In classical crossed mixed effects models (Montgomery (1998)) every ANOVA expected mean square has a contribution from the highest order variance component, typically containing measurement error.…”
Section: Squares and Sums Of Squaresmentioning
confidence: 99%
“…In studies of different economic processes the concept of sensitivity [22,23] of interrelation of various technical and economic indicators is used. It can be absolute (rate of change in the indicator in response to the change in the factor) and relative (elasticity showing percentage of change in the indicator in response to a one-percent change in the factor).…”
Section: Model Of Budget Sensitivitymentioning
confidence: 99%
“…In the following, a short introduction of the most important concepts concerning the FANOVA decomposition is given. A more extensive overview of the theory is beyond the scope of this paper-we refer to Muehlenstaedt et al, 17 Sobol 27 and Fruth et al 28 for a comprehensive summary.…”
Section: Fanova Graphsmentioning
confidence: 99%
“…Apart from the metamodel-based computational costs, it can be shown that choosing an appropriate TII estimation method guarantees a linear increase of complexity with increasing problem dimensions. See Fruth et al 28 for a review of the estimation procedure.…”
Section: Notes On Tii Estimationmentioning
confidence: 99%